Dinâmica da vacinação contra a Covid-19 - André Nagy; Fulano de Thal (Confins)
After a late and difficult start, Covid-19 vaccination is making rapid progress in Brazil. However, the distribution of those vaccinated is far from homogeneous, and changes over time. Based on SUS data we show progress in vaccination coverage. While in April 2021 rates were high in peripheral regions in July they had increased in the São Paulo-Mato Grosso do Sul axis, and even more so in October: by this date the entire state of São Paulo stands out for the dense and homogeneous coverage of its entire territory.